Predictors of recurrence after conversion therapy in unresectable hepatocellular carcinoma treated with HAIC, bevacizumab, and sintilimab - Liu, Chang-Fu; Zhao, Xiao-Hui; Zhu, Shi-Bo; Yu, Hai-Peng; Xing, Wen-Ge; Li, Hui-Kai (Frontiers in Immunology, 2025)
BackgroundConversion therapy with hepatic arterial infusion chemotherapy (HAIC) combined with bevacizumab and sintilimab has shown promise for unresectable hepatocellular carcinoma (uHCC). However, predictors of postoperative recurrence remain unclear.MethodsWe retrospectively analyzed 112 HCC patients treated with HAIC + bevacizumab + sintilimab followed by surgical resection. Patients were stratified into recurrence (n = 30) and non-recurrence (n = 82) groups. Demographics, laboratory values, and tumor measurements were collected before and after conversion therapy. Recurrence-free survival (RFS) was estimated by Kaplan–Meier analysis. Restricted cubic spline (RCS) logistic regression was used to identify thresholds for AFP decline and tumor size decline associated with 1-year recurrence. Multivariable logistic regression was used to determine independent predictors of recurrence.ResultsDuring conversion therapy, the non-recurrence group exhibited greater tumor shrinkage (5.67 ± 3.06 cm vs. 8.77 ± 3.92 cm; p<0.001), lower ALT (p=0.017), higher AST (p=0.008), and lower bilirubin (p=0.006). The median RFS was 22.2 months (95% CI: 18.3–28.0); the 1- and 2-year RFS rates were 71.7% and 46.9%, respectively. The RCS model showed that an AFP decline greater than 25% and tumor size reduction significantly lowered the risk of 1-year recurrence, but reductions in tumor size beyond 60% did not confer additional benefits in reducing recurrence risk. In multivariate analysis, tumor size decline ratio (OR=0.002; 95% CI: 0.000–0.117; p=0.002) and AFP decline ratio (OR=0.240; 95% CI: 0.067–0.862; p=0.029) during conversion therapy independently predicted a lower recurrence risk. Elevated post-therapy bilirubin level remained an adverse predictor (OR=1.020; 95%CI: 1.000–1.030; p=0.039). Adverse events were predominantly grade 1–2, and grade 3–4 adverse events were manageable and well-controlled.ConclusionsDecline ratios of tumor size and AFP during HAIC + bevacizumab + sintilimab conversion therapy were robust and independent predictors of 1-year postoperative recurrence in HCC. Monitoring of these dynamic biomarkers may guide optimal surgical timing and follow-up strategies.